Imageless vs Image-Based Computer Navigation in Total Hip Arthroplasty: An Intracase Comparison Shows Variability Between Technologies - Joseph T. Gibian, MD; Ryan J. Cone, MD; Matthew Booth, MD; Ling Chen, PhD; Kimberly A. Bartosiak, MD; Charles P. Hannon, MD, MBA; Ilya Bendich, MD, MBA (Arthroplasty Today, 2025)
Background: The use of computer navigation in total hip arthroplasty (THA) is on the rise. Computer navigation has 2 commonly utilized modalities, imageless (ILCN) and image-based (IBCN). The aim of this study was to compare ILCN and IBCN inclination and anteversion measurements when utilized in the same THA case. Methods: One-hundred consecutive primary or revision posterior THAs in which both ILCN and IBCN were utilized in the same case were included. Intraoperative ILCN and IBCN acetabular component inclination and anteversion measurements were recorded. Mean inclination and anteversion measurements from intracase ILCN and IBCN were compared. Discordant cases (>5° differences) were recorded; linear regression was used to determine if any confounding factors were associated with an increased risk of discordance. Results: There was no significant difference in mean inclination or anteversion between ILCN and IBCN. However, in 21% and 32% of cases, inclination and anteversion measurements, respectively, were discordant between ILCN and IBCN. Body mass index (P = .007) and prior lumbar spine fusion (P = .012) were correlated with increased discordance of anteversion. There was no association between discordance and dislocation rate. Conclusions: This intracase comparison of ILCN and IBCN demonstrates that in over 20% of cases, measurements between the 2 technologies are discordant. Risk factors for discordance include lumbar spine fusion and increased body mass index.